MONITORING TEGANGAN DAN ARUS LAMPU DC PADA PJU DENGAN SUMBER SOLAR CELL - Yuliananda, Subekti; Andriawan, Aris Heri; Ridho’i, Ahmad (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2016)
DC lamp voltage monitoring by microcontroller ATmega 328P through wireless zigbee is a monitoring tool that uses a DC lamp AVR microcontroller as a data processor, voltage and current sensors on the lights to detect the lamp current and voltage power supply, monitoring DC lights will transmit data to the monitoring in the form of a PC (Personal Computer) with the help of Visual Basic software, data transmission through wireless zigbee. Monitoring lamps DC serves to detect damage to the lamp and power supply, monitoring can be used to monitor street lighting that uses a DC lamp. Monitoring can monitor the DC lamp lights up to 50W and the power supply voltage is 12 VDC and can be informed remotely by using zigbee as a communication medium.Keywords: zigbee, lights, monitoring, ATmega